Increased Expression of Aldehyde Dehydrogenase 2 Reduces Renal Cell Apoptosis During Ischemia/Reperfusion Injury After Hypothermic Machine Perfusion. Issue 6 (19th November 2015) - Zhong, Zibiao; Hu, Qianchao; Fu, Zhen; Wang, Ren; Xiong, Yan; Zhang, Yang; Liu, Zhongzhong; Wang, Yanfeng; Ye, Qifa
Abstract: Hypothermic machine perfusion (MP) can reduce graft's injury after kidney transplantation; however, the mechanism has not been elucidated. In the past decade, many studies showed that aldehyde dehydrogenase 2 (ALDH2) is a protease which can inhibit cell apoptosis. Therefore, this study aims to explore whether ALDH2 takes part in reducing organ damage after MP. Eighteen healthy male New Zealand rabbits (12 weeks old, weight 3.0 ± 0.3 kg) were randomly divided into three groups: normal group, MP group, and cold storage (CS) group ( n = 6). The left kidney of rabbits underwent warm ischemia for 35 min through clamping the left renal pedicle and then reperfusion for 1 h. Left kidneys were preserved by MP or CS (4°C for 4 h) in vivo followed by the right nephrectomy and 24‐h reperfusion, and then the specimens and blood were collected. Finally, concentration of urine creatinine (Cr), blood urea nitrogen (BUN), and 4‐HNE were tested. Renal apoptosis was detected by TUNEL staining, and the expression of ALDH2, cleaved‐caspase 3, bcl‐2/ bax, MAPK in renal tissue was detected by immunohistochemistry or Western blot; 24 h after surgery, the concentration of Cr in MP group was 355 ± 71μmol/L, in CS group was 511 ± 44 μmol/L ( P < 0.05), while the BUN was 15.02 ± 2.34 mmol/L in MP group, 22.64 ± 3.58 mmol/L in CS group ( P < 0.05). The rate of apoptosis and expression of cleaved caspase‐3, p‐P38, p‐ERK, and p‐JNK in MP group was significantly lower than that in CS group ( P < 0.05), while expression of ALDH2 and bcl‐2/bax in MP group was significantly higher than that in CS group ( P < 0.05); expression of cleaved caspase‐3 in both MP and CS group significantly increased as compared with that in normal group ( P < 0.05). In conclusion, increased expression of ALDH2 can reduce the renal cell apoptosis through inhibiting MAPK pathway during ischemia/reperfusion injury (IRI) after hypothermic MP.